Improved HIV awareness and perceived empowerment to negotiate safe sex among married women in Ethiopia between 2005 and 2011. - Zaake De Coninck; Ibrahim A Feyissa; Anna Mia Ekström; Gaetano Marrone (PLoS ONE)
Introduction The HIV prevalence rate in Ethiopia for married (or cohabiting) women is 3 times that found amongst women who have never been married. While marriage used to be seen as a protective factor against HIV, evidence suggests that this is no longer necessarily the case. This study analyses the trend and socio-demographic determinants of HIV awareness and safe sex negotiation among married women in Ethiopia between 2005 and 2011. Methods Data from Ethiopian Demographic and Health Surveys conducted in 2005 and in 2011 were analysed. Socio-demographic variables as well as 'survey year' were selected to assess their interaction with selected HIV awareness and safe sex negotiation indicators. Multivariable regression analyses were performed. Odds ratios and confidence intervals were computed. Results A significant increase in knowledge of HIV and ability to negotiate safer sex occurred between 2005 and 2011 reflecting a positive trend in gender empowerment amongst married Ethiopian women. Some of these advancements were striking, for instance respondents were 3.6 times more likely to have "Heard of AIDS" in 2011 than in 2005. HIV awareness and safer sex negotiation were significantly associated with higher education, higher socioeconomic status, those who had heard of HIV, those of the Orthodox Christian faith, and (to some extent) those living in rural areas. Conclusion HIV awareness has increased significantly in Ethiopia over the last decade but married women are still disproportionately susceptible to HIV. Community programmes, already effective in Ethiopia, also need to target this vulnerable sub-group of women.